The Civil War as Total War: Madison, WI and the Creation of a Homefront - Barth, John E. (My University, 2010)
This paper studies Madison, Wisconsin during the Civil War and analyzes how it served as a "homefront" during the conflict. It examines how the media, government, soldier interaction, and involvement of women created an atmosphere that led to the mobilization of people in Madison. In a limited war, civilians whose relatives enlist in the military are those who have a high motivation to fight for the war effort at home. The mobilization of the entire citizenry of Madison supports that contention that the American Civil War was, in contrast, a "total war." This study supports this argument through the use of a variety of primary sources, including newspapers, political proclamations, and memoirs of the war. Madison, Wisconsin was on the U.S. frontier in the 1860s and thus completely separated from the battlefront. The arguments in this paper can thus be extrapolated to suggest that communities throughout the Union served similar functions in the Civil War. This project thus contributes a new perspective regarding the historical debate on the status of the Civil War as a total war.
Keywords: Madison (Wis.)--History--Civil War, 1861-1865; United States--History--Civil War, 1861-1865--War work; Total war